2002
DOI: 10.1111/j.1151-2916.2002.tb00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Andalusite‐Based High‐Alumina Castables

Abstract: Andalusite is easily converted to mullite and silica on heating. A better understanding of the mullitization mechanisms provides new information on use of this mineral in refractory castables. By using specific particle-size distributions for andalusite-based high-alumina castables, the primary mullite formation can be effectively enhanced by a secondary mullite reaction within castables matrices. The influence of ultrafine andalusite grains on thermomechanical properties of specimens is underlined by testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 7 publications
3
17
0
Order By: Relevance
“…The volumetric variation of the crystal phases alone, i.e. andalusite to mullite crystals, is -18%, while the glass volume variation is +22% (bulk densities of silica glass, andalusite and mullite are 2.2-2.6, 3.15 and 3.2 g/cm 3 , respectively) [23]. The differences in the densities cause expansion at higher temperatures (1350 ˚C).…”
Section: Effect Of Microsilica/cement Ratio On Permanent Linear Changmentioning
confidence: 98%
“…The volumetric variation of the crystal phases alone, i.e. andalusite to mullite crystals, is -18%, while the glass volume variation is +22% (bulk densities of silica glass, andalusite and mullite are 2.2-2.6, 3.15 and 3.2 g/cm 3 , respectively) [23]. The differences in the densities cause expansion at higher temperatures (1350 ˚C).…”
Section: Effect Of Microsilica/cement Ratio On Permanent Linear Changmentioning
confidence: 98%
“…The expelled silica-rich phase may react with alumina fines in the matrix forming mullite needles (secondary mullitization) which further strengthen the castable. Several recent investigations have shown that secondary mullitization is indeed promoted in very fine andalusite powder and promising properties of castables with fine andalusite were reported [2,4,6]. On the other hand, a negative effect of expelled silica on high temperature strength was reported for castables containing andalusite aggregates, as it was assumed to promote a liquid phase formation at service temperatures [3,7,8].…”
Section: Introductionmentioning
confidence: 98%
“…In aluminabased castables, high properties may be obtained using a micro-silica addition and alumina fines in the matrix. In a number of recent publications, the potential of incorporating very fine andalusite powder in castables as a source of mullite was explored [1][2][3][4][5][6]. On firing at temperatures above 1250-1300 °C, andalusite transforms to a mullite, releasing silica-rich amorphous phase.…”
Section: Introductionmentioning
confidence: 99%
“…Alumina-based refractories can be classified into low-alumina, containing less than 50% Al 2 O 3 , and high-alumina or bauxite, containing between 50 and 90% Al 2 O 3 . High-alumina refractories have widespread applications in high-temperature metal extraction processes due to their outstanding thermochemical and thermomechanical properties and stability (Rebouillat and Rigaud, 2002;Frulli, 2016). The typical chemical composition of refractory-grade bauxite consists of 85-90 wt.% Al 2 O 3 , 5-10 wt.% SiO 2 , 1-2wt.% Fe 2 O 3 , 3-4 wt.% TiO 2 , 0.4-0.8 wt.% CaO + MgO, and 0.20-0.8 wt.% K 2 O + Na 2 O (Nyoka et al, 2013).…”
Section: Introductionmentioning
confidence: 99%